Active Galactic Nuclei at All Wavelengths and from All Angles - Padovani, Paolo (Frontiers in Astronomy and Space Sciences, 2017)
AGN are quite unique astronomical sources emitting over more than twenty orders of magnitude in frequency, with different electromagnetic bands providing windows on different sub-structures and their physics. They come in a large number of flavors only partially related to intrinsic differences. I highlight here the types of sources selected in different bands, the relevant selection effects and biases, and the underlying physical processes. I then look at the ``big picture'' by describing the most important parameters one needs to describe the variety of AGN classes and by discussing AGN at all frequencies in terms of their sky surface density. I conclude with a look at the most pressing open issues and the main new facilities, which will flood us with new data to tackle them.